Out of equilibrium transport through an Anderson impurity: probing scaling laws within the equation of motion approach - Balseiro, Carlos Antonio (2010)
We study non-equilibrium electron transport through a quantum impurity coupled to metallic leads using the equation of motion technique at finite temperature T . Assuming that the interactions are taking place solely in the impurity and focusing on the infinite Hubbard limit, we compute the out of equilibrium density of states and the differential conductance G2(T, V ) in order to test several scaling laws. We find that G2(T, V )/G2(T, 0) is a universal function of both eV/TK and T/TK, TK being the Kondo temperature. The effect of an in-plane magnetic field on the splitting of the zero bias anomaly in the differential conductance is also analyzed. For a Zeeman splitting , the computed differential conductance peak splitting depends only on /TK, and for large fields approaches the value of 2. Besides studying the traditional two leads setup, we also consider other configurations that mimic recent experiments, namely, an impurity embedded in a mesoscopic wire and the presence of a third weakly coupled lead. In these cases, a double peak structure of the Kondo resonance is clearly obtained in the differential conductance while the amplitude of the highest peak is shown to decrease as ln(eV/TK). Several features of these results are in qualitative agreement with recent experimental observations reported on quantum dots.